Immunotherapy for Recurrent orthostatic cerebral hypo-perfusion syndrome in recurrent COVID-19 infection - Atakla, Hugues Ghislain; Souare, Ibrahima Sory; Noudohounsi, Mahugnon Maurel Ulrich Dénis; Cissé, Fodé Abass; Houinato, Dismand Stephan (Nepal Journal of Neuroscience, 2021)
Orthostatic hypotension, often interpreted as a drop in blood pressure as a person moves from lying or sitting to standing, has a direct impact on the brain. It results in a decrease in brain perfusion pressure and in many cases causes symptoms of transient cerebral hypo perfusion. This report treats a case of recurrent orthostatic hypotension in a field of recurrent Covid-19 infection, with a good clinical response to early immunotherapy. Signs of lung infection retroceded until complete disappearance under treatment with chloroquine sulfate and azythromycin. However, due to persistent signs of dysautonomy and paresthesias, we had subjected the patient to intravenous immunoglobulin immunotherapy with a good therapeutic response until the patient’s complete recovery 150 days after the start of treatment. The prognosis remains unknown at this time, as we do not yet have data from large-scale studies on this subject.